Ligand selectivity by seeking hydrophobicity in thyroid hormone receptor - Borngraeber, Sabine (National Academy of Sciences, 2003)
Selective therapeutics for nuclear receptors would revolutionize treatment for endocrine disease. Specific control of nuclear receptor activity is challenging because the internal cavities that bind hormones can be virtually identical. Only one highly selective hormone analog is known for the thyroid receptor, GC-24, an agonist for human thyroid hormone receptor β. The compound differs from natural hormone in benzyl, substituting for an iodine atom in the 3′ position. The benzyl is too large to fit into the enclosed pocket of the receptor. The crystal structure of human thyroid hormone receptor β at 2.8-Å resolution with GC-24 bound explains its agonist activity and unique isoform specificity. The benzyl of GC-24 is accommodated through shifts of 3–4 Å in two helices. These helices are required for binding hormone and positioning the critical helix 12 at the C terminus. Despite these changes, the complex associates with coactivator as tightly as human thyroid hormone receptor bound to thyroid hormone and is fully active. Our data suggest that increased specificity of ligand recognition derives from creating a new hydrophobic cluster with ligand and protein components.